Phase and electrical properties of PZT thin films embedded with CuO nano-particles by a hybrid sol-gel route - Sreesattabud T. (2014)
Pb(Zr0.52Ti0.48)O3 or PZT thin films embedded with CuO nano-particles were successfully prepared by a hybrid sol-gel process. In this process, CuO (0, 0.1, 0.2, 0.3, 0.4, 0.5 and 1 wt. %) nanopowder was suspended in an organometallic solution of PZT, and then coated on platinised silicon substrate using a spin-coating technique. The influence of CuO nano-particles' dispersion on the phase of PZT thin films was investigated. XRD results showed a perovskite phase in all films. At the CuO concentration of 0.4-1 wt. %, a second phase was observed. The addition of CuO nano-particles affected the orientation of PZT thin films. The addition was also found to reduce the ferroelectric properties of PZT thin films. However, at 0.2 wt. % CuO concentration, the film exhibited good ferroelectric properties similar to those of PZT films. In addition, the fatigue retention properties of the PZT/CuO system was observed, and it showed 14% fatigue at 108 switching bipolar pulse cycles while the fatigue in PZT thin films was found to be 17% at the same switching bipolar pulse cycles. © 2013 The Korean Institute of Metals and Materials and Springer Science+Business Media Dordrecht.